A pharmacovigilance study of vortioxetine based on data from the FDA adverse event reporting system - Miao Liu; Yang Xia; Wenwen Long; Xiaowen Han; Yu Xiong (Scientific Reports)
Abstract Vortioxetine is an antidepressant approved for the treatment of major depressive disorder (MDD). Given its widespread post-marketing clinical use, it is essential to explore its real-world safety. Reports were extracted from the FDA Adverse Event Reporting System (FAERS) from the third quarter of 2013 to the first quarter of 2025. Four disproportionality analysis methods, commonly used in pharmacovigilance to evaluate the relative reporting frequency of adverse events (AEs), were employed to identify AE signals associated with vortioxetine. These included the Reporting Odds Ratio (ROR), Proportional Reporting Ratio (PRR), Multi-item Gamma Poisson Shrink (MGPS), and Bayesian Confidence Propagation Neural Network (BCPNN). The median was used to describe the time to onset (TTO) of AEs, and Weibull distribution was employed to assess the trend of AE occurrence over time. In addition, sensitivity analyses were conducted to ensure the robustness of the findings. A total of 13,613 individual case safety reports (ICSRs) involving 34,156 AEs were analyzed. Females accounted for 60.9% of the reports, while males represented 26.5%. The median age of patients was 42 years (interquartile range: 26–59 years), with most cases (34.1%) in the 18–65 age group. The United States contributed the highest proportion of reports (77.4%). Common AEs included nausea (n = 2042, ROR = 5.11, PRR = 4.86, EBGM = 4.85, IC = 2.28), anxiety (n = 781, ROR = 5.3, PRR = 5.2, EBGM = 5.18, IC = 2.37 ), vomiting (n = 773, ROR = 3.23, PRR = 3.17, EBGM = 3.17, IC = 1.66), headache (n = 670, ROR = 1.96, PRR = 1.94, EBGM = 1.94, IC = 0.96), and somnolence (n = 212, ROR = 2, PRR = 1.99, EBGM = 1.99, IC = 0.99). Notably, several AEs not listed on the drug label, such as tinnitus (n = 79, ROR = 3.24, PRR = 3.24, EBGM = 3.23, IC = 1.69), urinary retention (n = 62, ROR = 3.57, PRR = 3.57, EBGM = 3.56, IC = 1.83), prolonged QT interval (n = 62, ROR = 3.14, PRR = 3.13, EBGM = 3.13, IC = 1.64), and restless legs syndrome (n = 48, ROR = 5.08, PRR = 5.08, EBGM = 5.06, IC = 2.34) were also identified. Most AEs occurred within the first month of treatment, with a median onset time of 15 days. Sensitivity analyses confirmed the consistency of these findings. This study provides new insights into the safety of vortioxetine and offers preliminary safety evidence. In addition, the findings may inform updates to prescribing information and guide post-marketing safety surveillance. However, the spontaneous nature of the FAERS database precludes establishing a causal relationship between vortioxetine and the reported AEs. Further prospective studies are needed to validate our findings.